UTILIZATION OF NEW MEDIA PODCAST BERIZIK (JOKING MUSIC CONTENT) IN DELIVERING MESSAGES ABOUT MUSIC - Radjagukguk, Djudjur Luciana; Pradana, Vian Nauval (JILPR Journal Indonesia Law and Policy Review, 2020)
The presence of podcasts can now be a new innovation in conveying messages, especially as a function of mass media in general, namely to entertain, educate, and provide information. Berizik Podcast (Joking Is It Muzik) is a podcast that contains music interspersed with stand-up comedian-style jokes. Fun Podcasts that discuss music often discuss domestic and foreign music, so this Podcast can be said to be an entertaining podcast and can provide information about music. In this case, podcast is included in the type of new media or New media, according to Pierre Levy, New Media has two views, namely social interaction and social integration, so that its use can be different from the media in general. The purpose of this study was to determine and analyze the use of Berizik new media podcast in conveying messages about music. This study uses a qualitative approach, namely the inductive thinking process which is related to the relationship between phenomena. This type of research used in descriptive research is based on interview data and documentation by presenting the results of the research in a narrative. The results of this study found that the use of Berizik's new media podcast in conveying messages about music was quite effective. In this case Berizik is utilized by the NOICE platform as an entertainment platform that can provide information about music to listeners, so as to provide new knowledge about music and also be entertained by comedy elements in Berizik's podcast.